Fish and invertebrate catch per unit of effort and biomass of three bottom trawl hauls in 2022, southern North Sea - Jens Floeter (PANGAEA, 2023)
During a MARSYS student training cruise (HE600) three bottom trawl hauls were conducted on 2022 June 3., 7. and 10. in the southern North Sea. The catch per unit of effort and biomass data originate from bottom trawl hauls (RV Heincke Schollensack, AWI), conducted with the Schollennetz from RV Heincke. The trawl ground rope was approx. 17 m, the vertical opening approx. 2 m and the cod end mesh size 1 cm. Tow duration was recorded for effort standardization.